Nuclear β‐catenin localization supports homology of feathers, avian scutate scales, and alligator scales in early development. Issue 3 (June 2015) - Musser, Jacob M.; Wagner, Günter P.; Prum, Richard O.
SUMMARY Feathers are an evolutionary novelty found in all extant birds. Despite recent progress investigating feather development and a revolution in dinosaur paleontology, the relationship of feathers to other amniote skin appendages, particularly reptile scales, remains unclear. Disagreement arises primarily from the observation that feathers and avian scutate scales exhibit an anatomical placode—defined as an epidermal thickening—in early development, whereas alligator and other avian scales do not. To investigate the homology of feathers and archosaur scales we examined patterns of nuclear β‐catenin localization during early development of feathers and different bird and alligator scales. In birds, nuclear β‐catenin is first localized to the feather placode, and then exhibits a dynamic pattern of localization in both epidermis and dermis of the feather bud. We found that asymmetric avian scutate scales and alligator scales share similar patterns of nuclear β‐catenin localization with feathers. This supports the hypothesis that feathers, scutate scales, and alligator scales are homologous during early developmental stages, and are derived from early developmental stages of an asymmetric scale present in the archosaur ancestor. Furthermore, given that the earliest stage of β‐catenin localization in feathers and archosaur scales is also found in placodes of several mammalian skin appendages, including hair and mammary glands, we hypothesize that a common skin appendage placode originated in the common ancestor of all amniotes. We suggest a skin placode should not be defined by anatomical features, but as a local, organized molecular signaling center from which an epidermal appendage develops.